A lethal model of Leptospira infection in hamster nasal mucosa - Jiaqi Wang; Wenlong Zhang; Zhao Jin; Yue Ding; Shilei Zhang; Dianjun Wu; Yongguo Cao (Public Library of Science (PLoS), 2022)
Leptospirosis is a fatal zoonosis caused by contact between skin or a mucosal surface and contaminated soil or water. Hamsters were infected by intraperitoneal injection fto establish experimental leptospirosis, which is not a natural route of infection. There are no reports of nasal mucosal infection in hamsters. In this study, infection of the nasal mucosa was performed to establish a model of natural infection. Both methods of infection can cause lethal models with similar symptoms in the later stages of infection, such as weight loss, blood concentration, increased neutrophils (GRAN), and decreased lymphocytes (LYM) in the blood, severe organ damage and liver function obstruction. The burden of Leptospira in the organs and blood was lower in the mucosal inoculation groups at 1 day after infection. However, mucosal infection induced a higher Leptospira burden in urine than intraperitoneal infection in the late stages of infection. After nasal mucosal infection, antibody levels were higher and lasted longer. These results indicated that the route of nasal mucosal infection is a good choice for studying leptospirosis in hamsters. Author summary The establishment of a leptospirosis experimental model is still key to elucidating the pathogenesis of leptospirosis. Hamsters were infected by intraperitoneal injection to establish experimental leptospirosis, although this is not a natural route of infection. The transmission characteristics of Leptospira and the disease progression in hamsters infected by a natural transmission route (e.g. through mucosal surfaces) had not been explored. In this study, we compared the dynamics of Leptospira infection in hamsters inoculated via the nasal mucosa or by intraperitoneal inoculation, and compared the burden of Leptospira and the level of antibodies produced with disease progression, such as body weight, serology, haematological changes and histopathological changes. Our data suggested that there are significant differences in the dynamics of infection between intraperitoneal and mucosal infection pathways. Although the result was the same in the later stage of infection, the course of mucosal infection was slower, which may better recapitulate the natural history of the disease, assist in studying kidney disease caused by Leptospira, and provide an animal model for the study of leptospirosis mucosal immunity.